THE CONCEPT «ONE BELT, ONE ROAD» (OBOR): BACKGROUND AND REALITIES - KUKHARSKA, NATALIIA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article contains an analysis of China’s economic development over the years of reform and opening up policies (1978-2018). The paper presents the main drivers of the rapid economic growth of China, which allowed to achieve significant results, namely: investment in research and development (R&D), as a result of which China became the third country in the world; the banking system, which is represented by corporate giants occupying the highest steps in the rating of 2000 largest companies by Forbes magazine; the army, which is the second after the United States, and the country’s military reform, which resulted in the creation of naval infrastructure in the key regions for the PRC - the western part of the Pacific Ocean, the Indian Ocean, and the Red Sea. The author reveals the essence of China’s large-scale infrastructure project "One Belt, One Road" (OBOR). The OBOR goal is formulated, upon achieving which China changes the global infrastructure for its development for the long term, using globalization 2.0 (in which China will lead and determine the course of the world process) and the modern interdependence of the countries of the world. The author substantiates the main goals of the OBOR concept: building a transport infrastructure for the development of the "New Silk Road"; active work in the field of energy; expanding trade cooperation; creation of projects of cultural and humanitarian exchanges. For each challenge, specific achievements that have already been achieved by China are listed. The article reveals the economic approaches of the PRC to entering the markets of countries in various regions of the Eastern Hemisphere (Western and Southern Europe, countries of Central and Eastern Europe, Southeast Asia and Africa, as well as cooperation between the PRC and Russia. Federation) and substantiates the spheres of its interests in relation to these countries. The paper substantiates the logistical importance of Ukraine for the "One Belt, One Road" project and identifies the problems that need to be overcome for the possible integration of Ukraine into the central land route OBOR - "New Eurasian Land Bridge" through Kazakhstan - RF - Belarus - Poland.